2021
DOI: 10.1111/avj.13102
|View full text |Cite
|
Sign up to set email alerts
|

Pet ownership and mental health during COVID‐19 lockdown

Abstract: Owning a pet has often been associated with improved mental health among owners, including enhanced quality of life, and decreased levels of depression and loneliness. The aim of this study was to identify whether owning a cat and/or dog was associated with better psychological wellbeing during a strict lockdown period in Victoria, Australia, during the COVID-19 pandemic. Data were analysed from a large-scale mental health study: the COvid-19 and you: mentaL heaLth in AusTralia now survEy (COL-LATE). The impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 17 publications
1
49
0
Order By: Relevance
“…Two studies reported that pet owners perceived that their mental tensions diminished due to the presence of their dog and the ability to walk them in addition to reporting a smaller decrease in mental health and a smaller increase in loneliness during lockdown [12,13]. In contrast, another study found pet ownership to be associated with poorer QoL but not with resilience and loneliness [14]. Multiple reasons could have led to these differences, including different studied populations and contexts (Australia and UK), use of different mental health and well-being scales, and the inclusion of different confounder sets in the final models [12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported that pet owners perceived that their mental tensions diminished due to the presence of their dog and the ability to walk them in addition to reporting a smaller decrease in mental health and a smaller increase in loneliness during lockdown [12,13]. In contrast, another study found pet ownership to be associated with poorer QoL but not with resilience and loneliness [14]. Multiple reasons could have led to these differences, including different studied populations and contexts (Australia and UK), use of different mental health and well-being scales, and the inclusion of different confounder sets in the final models [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, those most affected by the confinement were also the ones who felt more supported by their pets during that time. The impact of pet or dog ownership on mental health has also been assessed since the beginning of the pandemic in Australia and the UK and in a multi-country (Europe, Americas, Asia, and Australia) study [ 12 , 13 , 14 ]. These studies found that companion animal owners perceived that their mental health improved due to their dog or the ability to walk them [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though we are aware that dog owners experienced advantages in having a dog by their side, in terms of feeling of loneliness attenuation and, therefore, protection from the development of mental disorders such as depression [5], studies that present only positive outcomes of dog ownership have been targeted on the adult population or, at least, adolescents [5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Pets during the pandemic era are reported in the literature as having an important role in mitigating loneliness and safeguarding their owners' mental health. This emotional buffering effect is explained by the opportunities that pets give people to touch and feel another living creature in the house, and moreover, the necessity of having to take dogs out for a walk gives the dog owner an opportunity to continue having social interactions with other people in spite of lockdown [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The particular areas of concern were similar to those shown in previous studies, around access to veterinary treatment [ 29 ] and effects on animal exercise, activity and otherwise meeting the needs of pets [ 30 ]. One study has suggested that pet ownership during COVID was associated with lower life satisfaction, perhaps because of some of these areas of concern [ 54 ], but the responses from our questionnaire were overall more positive than this, with lower rates of concerns and considerations regarding potentially giving up their pets among our respondents. Numbers of people with concerns and numbers of concerns per concerned person were not different between PwMS and controls, suggesting that having MS did not make people be more likely to have concerns about the effects of COVID-19 on their pet, or to have a greater number of concerns.…”
Section: Discussionmentioning
confidence: 76%